Bionanotechnology - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Safriza, Baharuddin; Muhammad Najib, Muhammad Nor; Noor Azhar, Abd. Rasid (Penerbit UMP, 2009)
Bionanotechnology is a subset of nanotechnology: atom-level engineering and manufacturing using biological precedents for guidance. It is also closely married to biotechnology, but adds the ability to design and modify the atomic-level details of the objects created.